Shear alignment of fullerenes in nanotubular supramolecular complexes - Kincer, MR; Choudhury, R; Srinivasarao, M; Beckham, H; Briggs, G; Porfyrakis, K; Bucknall, D (Elsevier, 2015)
Supramolecular complexes of C60 and C70 encapsulated within the cavity created by the helical superstructure of syndiotactic poly(methyl methacrylate) (s-PMMA) were aligned by elevated-temperature electrospinning. Using 13C solid-state NMR, encapsulation of C60 within the nanotubular cavity was confirmed by downfield chemical shifts and significantly shorter spin-spin relaxation times compared to C60 physically mixed with s-PMMA. Thermal analysis revealed a melting endotherm at 180°C for the C60/s-PMMA electrospun fibers that is consistent with formation of the nanotubular supramolecular complex. Based on the syndiotactic content of the s-PMMA and the gravimetrically determined fullerene content in the electrospun fibers, 82% of the nanocavity is filled with C60, dropping to 55% filling with C70. The fibers were macroscopically aligned by electrospinning onto a split collector plate for analysis of molecular alignment. Wide-angle X-ray scattering azimuthal scans revealed high degrees of molecular-level alignment, with an order parameter of 0.70 for the C60/s-PMMA nanopods.